The Cost of Leasing: Comment and Correction. - Beechy, Thomas H. (The Accounting Review, 1970)
The article responds to a comment presented by professor G. B. Mitchell regarding the methods used in evaluating financial leases. Mitchell's basic objection to the author's method of analysis is that he did not allow for the tax deductibility of interest and therefore did not obtain a correct after-tax implicit interest rate. It is because the method gives a before-tax rate which is directly comparable to the before-tax marginal cost of borrowing; it was never intended to yield an after-tax rate on the belief that managers are more accustomed to dealing with before-tax rates. Therefore the gross amount of the interest is allowed to flow through to the final cash flow, yielding a before-tax interest calculation. Unfortunately, it works exactly right only when the lease payments are identical to the equivalent loan repayments. If it were, then a simple investment involving a cash outflow in the first year followed by inflows for the rest of the project's life should be evaluated by discounting as a form of financing. Therefore it seems that, although Mitchell's objections to the internal rate of return are technically correct, they are substantially irrelevant to the problem of lease evaluation.